Can the State be held accountable for water pollution? A critical analysis of legal alternatives available to prospective litigants - Bond-Smith, Marguerite (Institute of Marine and Environmental Law, 2026)
Water is considered to be one of the most essential of all natural resources 1 and its importance in the perpetuation of life is incontrovertible. The 'human poverty index' formulated by the United Nations Development Programme, lists a decent standard of living as one of the three essentials for human life, which in turn is determined by, amongst other, access to safe water. Water is one of the key resources determining the health and wealth of a nation resulting in management of the resource to ensure sustainable use being 'vital'.2 The United Nations Committee on Economic, Social and Cultural Rights significantly links the right to water, as a limited natural resource, the enjoyment of health and other human rights by stating that the right to water is indispensable to leading a life in human dignity and is a prerequisite for the realization of other human rights. 3 • Assuming current economic and population growth, it is estimated that by 2030 water supplies will only satisfy 60 percent of global demand and less than 50 percent in developing regions, including South Africa, where water supply is already under stress.4 Blignaut and Van Heerden describe our water situation as 'precarious'. 5 The situation is further exacerbated by the uneven distribution of water which engenders water scarcity, which in turn induces more stringent rules for water use.6 Blignaut and Van Heerden7 state that 'the availability of water of acceptable quality is predicted to be the single greatest and most urgent development constraintfacing South Africa'.